Extra-Small Gold Nanospheres Decorated With a Thiol Functionalized Biodegradable and Biocompatible Linear Polyamidoamine as Nanovectors of Anticancer Molecules - Bloise, Nora; Massironi, Alessio; Della Pina, Cristina; Alongi, Jenny; Siciliani, Stella; Manfredi, Amedea; Biggiogera, Marco; Rossi, Michele; Ferruti, Paolo; Ranucci, Elisabetta; Visai, Livia (Frontiers in Bioengineering and Biotechnology, 2020)
Gold nanoparticles are elective candidate for cancer therapy. Current efforts are devoted to developing innovative methods for their synthesis. Besides, understanding their interaction with cells have become increasingly important for their clinical application. This work aims to describe a simple approach for the synthesis of extra-small gold nanoparticles for breast cancer therapy. In brief, a biocompatible and biodegradable polyamidoamine (named AGMA1-SH), bearing 20%, on a molar basis, thiol-functionalized repeat units, is employed to stabilize and coat extra-small gold nanospheres of different sizes (2.5, 3.5, and 5 nm in gold core), and to generate a nanoplatform for the link with Trastuzumab monoclonal antibody for HER2-positive breast cancer targeting. Dynamic light scattering, transmission electron microscopy, ultraviolet visible spectroscopy, X-ray powder diffraction, circular dichroism, protein quantification assays are used for the characterization. The targeting properties of the nanosystems are explored to achieve enhanced and selective uptake of AGMA1-SH-gold nanoparticles by in vitro studies against HER-2 overexpressing cells, SKBR-3 and compared to HER-2 low expressing cells, MCF-7, and normal fibroblast cell line, NIH-3T3. In vitro physicochemical characterization demonstrates that gold nanoparticles modified with AGMA1-SH are more stable in aqueous solution than the unmodified ones. Additionally, the greater gold nanoparticles size (5-nm) is associated with a higher stability and conjugation efficiency with Trastuzumab, which retains its folding and anticancer activity after the conjugation. In particular, the larger Trastuzumab functionalized nanoparticles displays the highest efficacy (via the pro-apoptotic protein increase, anti-apoptotic components decrease, survival-proliferation pathways downregulation) and internalization (via the activation of the classical clathrin-mediated endocytosis) in HER-2 overexpressing SKBR-3 cells, without eliciting significant effects on the other cell lines. The use of biocompatible AGMA1-SH for producing covalently stabilized gold nanoparticles to achieve selective targeting, cytotoxicity and uptake is completely novel, offering an important advancement for developing new anticancer conjugated-gold nanoparticles.